Transition of electron transport process in Be-doped low-temperature-grown GaAs layer - Mohamed, Mohd Ambri; Otsuka, Nobuo; Pham, Tien Lam (American Institute of Physics, 2013)
Effects of the structure change of antisite-As (AsGa) defects on the electron transport property in Be-doped low-temperature-grown GaAs layers were investigated. In this material AsGa atoms cooperatively change their positions between substitutional and interstitial sites. We found an abrupt change in the resistance of a sample at a temperature around 3 K where a discontinuous decrease of the magnetization was also observed. The mechanism of the transition of the electron transport property is explained by first-principles calculations of the electron state of an AsGa atom accompanied with a shallow acceptor Be atom. At the transition, AsGa+ ions are cooperatively displaced to interstitial sites and become neutral atoms, which results in generation of holes in the valence band. The mechanism of the discontinuous change of the electron transport process in this material is discussed in connection with existing mechanisms such as those of metal-insulator transitions.